ダイ 28 ジ ナンキョク チイキ カンソク タイ アスカ カンソク キョテン チガク ブモン ホウコク 1987 - 渋谷, 和雄; シブヤ, カズオ; 酒井, 量基; サカイ, リョウキ; Shibuya, Kazuo; Sakai, Ryoki (1989)
P(論文) 第28次「あすか観測拠点」越冬において地学部門は固体地球物理観測を重点的に実施した。観測項目としては(1) GPS干渉測位を利用したL0点でのジオイド高決定, シール岩測地基準点における海抜高度決定, 光波測距やNNSSトランスロケーションによる基線長収束精度とGPS干渉測位との比較, (2) ピラタス機による航空磁気測量とアイスレーダー観測, 並びにセスナ機による氷床形態観測, (3) ラコステ・ロンバーグG型重力計による地球潮汐観測(6カ月), (4) Lルート, ABルート上での重力測定(1kmごと), (5) シール岩における地磁気絶対測定, (6) ABルート(2kmごと)や, いくつかの測点での全磁力観測と帯磁率測定, (7) 12台の地震計による多点地震観測(500m×1200m区域内に設置), などがあげられる。この報告は各観測項目につき, 観測の目的, 方法, 技術的問題点等をまとめたものである。 During the wintering season of the 28th Japanese Antarctic Research Expedition, we concentrated on observations of solid earth geophysics at Asuka Station and in the Sφr Rondane Mountains region. The item of observation includes : (1) GPS interferometry for determining geoid height at L0 point, elevation above sea level at the Seal geodetic control station, performance test of the accuracy of the baseline length determination as compared with those by optical distance meter and NNSS translocation, (2) airborne proton magnetic survey and radio-echo sounding by Pilatus Porter PC-6,and surface feature recording by Cessna 185F, (3) 6 months' earth tide observation by the use of a LaCoste & Romberg G-type gravity meter, (4) gravity measurement on the L- and AB-routes at intervals of 1km, (5) installation of a geomagnetic control station at the Seal Rock, (6) total magnetic intensity and magnetic susceptibility measurements on the AB-route and/or selected several stations in the region concerned, (7) seismic observation by arrayed 12 seismographs in the area 500m by 1200m to the south of Asuka Station. This report briefly describes objective, method, technical problem, etc. of each item of observation. departmental bulletin paper